2012
DOI: 10.3136/fstr.18.705
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination in Retail Foods Purchased in Thailand

Abstract: The loss of quality or quantity of raw foods caused by spoilage bacteria is a major problem, especially in developing countries. Evaluation of the frequency and level of bacterial contamination and/or identification of the contaminating bacteria are keys to solving this problem. The objective of this study was to evaluate the prevalence and types of contaminating bacteria in retail foodstuffs in Thailand. Foods in four categories (137 samples total) including meat (51 samples), vegetables (38 samples), fish or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…Likewise, 48.95% of fish and fish products from Punjab, India (Gupta et al, 2013); and 38.8% of fish and shellfish Mangalore, India (Kumar et al 2005) have been reported as E. coli positive. Ananchaipattana et al, (2012) also reported the highest presence (70%) of E. coli from seafood from retail markets (Open and supermarket) in Thailand. It was seen that; a higher isolation rates of E. coli have been reported in warmer climate countries.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, 48.95% of fish and fish products from Punjab, India (Gupta et al, 2013); and 38.8% of fish and shellfish Mangalore, India (Kumar et al 2005) have been reported as E. coli positive. Ananchaipattana et al, (2012) also reported the highest presence (70%) of E. coli from seafood from retail markets (Open and supermarket) in Thailand. It was seen that; a higher isolation rates of E. coli have been reported in warmer climate countries.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of staphylococci on seafood is not unusual. Indeed, [50] reported the isolation of Staphyococus lentus, S. sciuri and S. xylosus from fish and seafood samples (22% of the total) from Thailand. However, Staphylococcus is not usually regarded as an indigenous component of the microflora of fish, and may well reflect contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that B. cereus was the most prevalent in fermented meat and fish samples in Thailand Ananchaipattana et al, 2012 . In this case, fermented vegetables were contaminated also at high level rate of B. cereus 31% .…”
mentioning
confidence: 99%
“…Referring the methods used for the surveillances of Thai raw foods Ananchaipattana et al 2012 , E. coli, Salmonella spp., C. sakazakii, Enterococcus spp., Staphylococcus spp. Bacillus spp.…”
mentioning
confidence: 99%